2016
DOI: 10.1515/rrlm-2016-0021
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic study of carbapenem-resistant Pseudomonas aeruginosa strains isolated from hospitalized patients

Abstract: Introduction: Nosocomial infections caused by Pseudomonas aeruginosa producing carbapenemases represent an important cause of morbidity and mortality among immunosuppressed patients. The aim of our study was to detect the production of metallo-carbapenemases (MBLs) by phenotypic methods and to detect the presence of the MBLs encoding genes (blaIMP and blaVIM) by PCR in P. aeruginosa strains isolated from hospitalized patients to the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…P. aeruginosa exhibit high adaptation ability to enormously different settings owing to its varying potential of virulence factors plus its intrinsic resistance to several antibiotics. Inducible chromosomal AmpC beta -lactamases and efflux pumps systems are among the most frequent mechanisms of intrinsic resistance in P. aeruginosa isolates (3,4). The treatment of P.aeruginosa infections is challenging since acquired resistance can develop against broad-spectrum penicillins, extended-spectrum cephalosporins, monobactams, aminoglycosides and colistin which are applied as treatment alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…P. aeruginosa exhibit high adaptation ability to enormously different settings owing to its varying potential of virulence factors plus its intrinsic resistance to several antibiotics. Inducible chromosomal AmpC beta -lactamases and efflux pumps systems are among the most frequent mechanisms of intrinsic resistance in P. aeruginosa isolates (3,4). The treatment of P.aeruginosa infections is challenging since acquired resistance can develop against broad-spectrum penicillins, extended-spectrum cephalosporins, monobactams, aminoglycosides and colistin which are applied as treatment alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to clinical studies, there needs to be more information regarding the ARG reservoirs in the wastewater network in Romania. Our research team showed a high repertoire of ARGs and virulence markers in K. pneumoniae ST101 isolated from intrahospital infections and wastewater samples collected from the influent and, respectively, from the effluent of hospital collecting sewage tanks in the southern regions of Romania; the transmission of MDR, carbapenemase and ESBL-producing K. pneumoniae ST101 from hospital to hospital effluent; and its persistence after the chlorine treatment [339,344]. In the country's central region, a chlorinated wastewater treatment system from a public hospital revealed the presence of the following carbapenemase and ESBL-encoding genes in the influent: bla PER , bla VIM , bla NDM-1 , and bla SHV .…”
Section: Antibiotic Resistance In Gram-negative Escape Pathogens In W...mentioning
confidence: 92%
“…Among the biological effect of EOs, the antimicrobial effect is, by far, one of the most studied. The emerge of multiresistant bacterial and fungal species involved in life-threatening infections maintain the interest on the discovery of new antibacterial and antifungal compounds [7,30]. The antibacterial effect of black cumin EO against Staphylococcus aureus is due to thymoquinone, carvacrol, and pcymene [33].…”
Section: Introductionmentioning
confidence: 99%